Renewal in European local democracies : Puzzles, dilemmas and options - Daemen, Harry; Schaap, Linze (Urban and Regional Research International, 2012)
This book explores the dynamics of democratic reform processes in  European local government. On the basis of analyses of theoretical challenges to present developments, the book pays attention to processes of democratic innovation inspired by classical representative democracy and by new forms of democracy influenced by notions of governance, participation, e-governance, empowering civil society and the like.  Also attention is given to the role of regionalization and of leader- ship in efforts to revitalize local democracy. Cases from all over Europe are being studied.